Safety and Immunogenicity of Modified Vaccinia Ankara-Bavarian Nordic Smallpox Vaccine in Vaccinia-Naive and Experienced Human Immunodeficiency Virus-Infected Individuals: An Open-Label, Controlled Clinical Phase II Trial. (5th May 2015) - Overton, Edgar Turner; Stapleton, Jack; Frank, Ian; Hassler, Shawn; Goepfert, Paul A; Barker, David; Wagner, Eva; von Krempelhuber, Alfred; Virgin, Garth; Weigl, Josef; Meyer, Thomas Peter; Müller, Jutta; et al.
Abstract: Background: First- and second-generation smallpox vaccines are contraindicated in individuals infected with human immunodeficiency virus (HIV). A new smallpox vaccine is needed to protect this population in the context of biodefense preparedness. The focus of this study was to compare the safety and immunogenicity of a replication-deficient, highly attenuated smallpox vaccine modified vaccinia Ankara (MVA) in HIV-infected and healthy subjects. Methods: An open-label, controlled Phase II trial was conducted at 36 centers in the United States and Puerto Rico for HIV-infected and healthy subjects. Subjects received 2 doses of MVA administered 4 weeks apart. Safety was evaluated by assessment of adverse events, focused physical exams, electrocardiogram recordings, and safety laboratories. Immune responses were assessed using enzyme-linked immunosorbent assay (ELISA) and a plaque reduction neutralization test (PRNT). Results: Five hundred seventy-nine subjects were vaccinated at least once and had data available for analysis. Rates of ELISA seropositivity were comparably high in vaccinia-naive healthy and HIV-infected subjects, whereas PRNT seropositivity rates were higher in healthy compared with HIV-infected subjects. Modified vaccinia Ankara was safe and well tolerated with no adverse impact on viral load or CD4 counts. There were no cases of myo-/pericarditis reported. Conclusions: Modified vaccinia Ankara was safe and immunogenic in subjects infected with HIV and represents a promising smallpox vaccine candidate for use in immunocompromised populations.